### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The derivative of e^x is e^x.

To prove the formula for the derivative of e^x, we start with the definition of the derivative:

f'(x) = lim(h->0) [f(x+h) - f(x)]/h

Let f(x) = e^x, then

f'(x) = lim(h->0) [e^(x+h) - e^x]/h

Using the properties of exponents, we can simplify this expression:

f'(x) = lim(h->0) [e^x * e^h - e^x]/h

f'(x) = lim(h->0) [e^x * (e^h - 1)]/h

Now we can use L'Hopital's rule to evaluate the limit:

f'(x) = lim(h->0) [e^x * e^h]/1

f'(x) = e^x * lim(h->0) e^h

Since lim(h->0) e^h = 1, we have:

f'(x) = e^x

Therefore, the formula for the derivative of e^x is e^x.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...